Ethnic stereotypes the role of contact - Gardner, R. C.; Taylor, D. M.; Santos, Emma (Philippine Journal of Psychology, 1969)
An interpretation is proposed which considers ethnic stereotypes as inferences about groups made from information obtained. Contact is viewede simply as one way of obtaining information and its role in stereotype change is seen as depending upon the nature of the contact. It is hypothesized that consensus in the stereotype will develop when many members of the stereotyping group share common information about the stereotyped group; heterogeneity of experiences will result in a lack of consensus. This interpretation was supported with data obtained from two groups of American teachers; one which lived in the Philippines for nine weeks (Contact group), and one which did not (No Contact group).